Nutrition and Physical Activity on Hypertension: Implication of Current Evidence and Guidelines - Castro, Iran; Waclawovsky, Gustavo; Marcadenti, Aline (Current Hypertension Reviews, 2015)
Hypertension (HTN) is the leading cause of worldwide mortality and is responsible for approximately 40% of deaths from cardiovascular disease, chronicle kidney disease (CKD) and type 2 diabetes mellitus (T2DM) according to the World Health Organization (WHO). It is known that about 80% of all mortality from cardiovascular disorders could be prevented if a healthy diet and higher levels of physical activity were included among general population’s lifestyle. Besides, guidelines for the treatment and control of HTN were recently modified for adequate nutritional and physical activity recommendations highlighted in meta-analysis and strong evidences such as randomized clinical trials. Therefore, to discuss nutrition and physical activity in the context of HTN seems to be crucial.
Keywords: muscle stretching exercises